2021
DOI: 10.3389/fmicb.2021.667096
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Resistance Genes in Bacteria Isolated From Japanese Honey, and Their Potential for Conferring Macrolide and Lincosamide Resistance in the American Foulbrood Pathogen Paenibacillus larvae

Abstract: American foulbrood (AFB) is the most serious bacterial disease of honey bee brood. Spores of the causative agent Paenibacillus larvae are ingested by bee larvae via brood foods and germinated cells proliferate in the larval midgut. In Japan, a macrolide antibiotic, tylosin, is used as the approved prophylactic for AFB. Although tylosin-resistant P. larvae has yet to be found in Japan, it may emerge in the future through the acquisition of macrolide resistance genes from other bacteria, and bacteria latent in b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 63 publications
(102 reference statements)
0
18
0
Order By: Relevance
“…The representative strains of P. larvae and M. plutonius listed in Table 1 were used in sensitivity tests of the newly developed multiplex PCR assay. Sixty-five other bacterial strains, including those isolated from Japanese honey [ 43 ] and honey bees [ 3 ], were used in addition to the foulbrood pathogens for specificity tests. Strains ATCC 6344 and ATCC 64, the type strains of Paenibacillus alvei and Brevibacillus laterosporus , respectively, were purchased from the American Type Culture Collection ( Supplementary Table 1 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The representative strains of P. larvae and M. plutonius listed in Table 1 were used in sensitivity tests of the newly developed multiplex PCR assay. Sixty-five other bacterial strains, including those isolated from Japanese honey [ 43 ] and honey bees [ 3 ], were used in addition to the foulbrood pathogens for specificity tests. Strains ATCC 6344 and ATCC 64, the type strains of Paenibacillus alvei and Brevibacillus laterosporus , respectively, were purchased from the American Type Culture Collection ( Supplementary Table 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…To assess the sensitivity of the multiplex PCR assay, genomic DNA was manually extracted from representative P. larvae strains cultured on MYPGP agar [ 13 ] at 35°C for two days under air plus 5% CO 2 conditions and M. plutonius strains cultured on KSBHI agar [ 4 ] at 35°C for three days under anaerobic conditions according to the methods described by Okamoto et al . [ 43 ] and Arai et al . [ 4 ], respectively.…”
Section: Methodsmentioning
confidence: 99%
“…These genes, which have a colloquial naming system based on discovery, can encode for a series of protective functions such as efflux, ribosomal modification proteins, and antibiotic destruction. In the context of honey bee health, OTC-resistance has been observed in Paenibacillus larvae , the causative agent of AFB disease, resulting from plasmid-encoded tetracycline resistance through the tetL gene 13 . Additionally, a series of Bacillus cereus strains isolated from honey were found to carry tetracycline resistance genes, including tetL and tetK 14 .…”
Section: Introductionmentioning
confidence: 99%
“…For example, erm genes, a major source of MLS B resistance, encode for rRNA methyltransferases that add one or two methyl groups onto the 23S rRNA, preventing the antibiotics from binding their target 18 . While no TYL or LMC-resistant P. larvae or M. plutonius have been identified, bacteria isolated from honey encode for MLS B resistance genes, including plasmid-borne 23S rRNA methyltransferases such as ermC 13 . Additionally, a recent study found M. plutonius isolates resistant to the macrolide antibiotic, mirosamicin 20 .…”
Section: Introductionmentioning
confidence: 99%
“…Resistance or low susceptibility of Paenibacillus spp. to clindamycin 22,31,33 and lincomycin 21 has been reported from various hosts and sources, suggesting that intrinsic resistance to lincosamides may exist, although the underlying mechanisms remain to be explored.…”
mentioning
confidence: 99%